PENGARUH PENERAPAN FINTECH, DANA PIHAK KETIGA, DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS - Ilham Suwanderi; Lindrianasari Lindrianasari; Niken Kusumawardani (Faculty of Economics and Business, 2020)
Profitability has information to determine the level of profit that the company recieves in a certain period of time and the productivity of the use of comapny’s funds, both loan capital and own capital, which can be used by investors and potential investors as a basis for making decision in investing.This studi aims to determine the extent to which the application of fintech affects the profitability, finding out to what extent third party funds affects the profitability, and to find out to what extent does operational efficiency affects profitability of Banking Companies listed in IDX in year 2014-2018. Samples in this research is chosen using purposive sampling method, and obtained 102 samples. The result shows that the application of financial technology, third party funds, and operational efficiency has a positive and significant effect on profitability.